Developing your conflict competence : a hands-on guide for leaders, managers, facilitators, and teams - Runde, Craig E., 1951- (Jossey-Bass business & management series., 2010)
"Survey after survey supports the notion that conflict is all around us. So the question isn't one of whether or not you'll experience conflict or how to reduce or avoid it. Instead, the question is what will you get out of conflict when it does occur. Depending on how you respond, that something can be good or bad, constructive or destructive, invigorating or can be good or bad, constructive or destructive, invigorating or debilitating"--Introduction.